2022
DOI: 10.1098/rsos.220839
|View full text |Cite
|
Sign up to set email alerts
|

Growing up in a crowd: social environment shapes the offspring's early exploratory phenotype in a colonial breeding species

Abstract: In colonial breeding species, the number of adverse social interactions during early life typically varies with breeding density. Phenotypic plasticity can help deal with this social context, by allowing offspring to adjust their behaviour. Furthermore, offspring may not be unprepared since mothers can allocate resources to their embryos that may pre-adjust them to the post-hatching conditions. Thus, we hypothesize that lesser black-backed gull chicks raised in dense breeding areas, with greater exposure to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…However, chicks do not necessarily hatch unprepared for this environment, as mothers can allocate hormones or other components to their eggs that can prepare their offspring for the conditions they are likely to encounter after hatching [4042]. In support of this, pre-natal breeding density significantly predicted chick exploration behaviour in the open field test with chicks from the same colony, including individuals from this study [32], with pre- and post-natal social environment contributing almost equally to chick exploration behaviour. While this suggests that offspring may indeed benefit from pre-natal programming when post-natal conditions match pre-natal conditions, we can only speculate why we did not find a similar pre-natal effect when we directly tracked chicks in their post-natal social environment.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…However, chicks do not necessarily hatch unprepared for this environment, as mothers can allocate hormones or other components to their eggs that can prepare their offspring for the conditions they are likely to encounter after hatching [4042]. In support of this, pre-natal breeding density significantly predicted chick exploration behaviour in the open field test with chicks from the same colony, including individuals from this study [32], with pre- and post-natal social environment contributing almost equally to chick exploration behaviour. While this suggests that offspring may indeed benefit from pre-natal programming when post-natal conditions match pre-natal conditions, we can only speculate why we did not find a similar pre-natal effect when we directly tracked chicks in their post-natal social environment.…”
Section: Discussionmentioning
confidence: 65%
“…On the one hand, lower movement activity would reduce the likelihood of crossing territorial boundaries, and as such, reduce the probability of an aggressive encounter. Consistent with this idea, we have recently shown that gull chicks reared at high breeding densities in a colony exhibit less exploratory activity in novel environments [32]. Furthermore, the early-life social environment may affect resilience to (social) stress [33] or anxiety, with the latter again facilitating avoidance of aggressive interactions [33,34] (but see [32]).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations